2016
DOI: 10.1002/adma.201600088
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐ and Micro‐Auxetic Plasmonic Materials

Abstract: and epoxy-resin casting.[ 19 ] Soft lithography, [ 12 ] femtosecond laser ablation, [ 13 ] and digital micromirror device projection printing [ 14 ] have allowed the fabrication of negative Poisson's ratio structures with characteristic sizes of hundreds of micrometers. Smaller dielectric auxetics with unit cells on the order of 100 µm have been made by laser micromachining, [ 15 ] while dielectric auxetics with a characteristic size of 10 µm have been realized by direct laser writing. [ 16 ] However, negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…The significance of this work to a wide variety of technological application is enhanced by the recent fabrication of mechanical meta-materials on micro/nano scale through use of nanomembrane technologies 9 and digital printing techniques 55 57 . The use of nanomembrane technologies restricts the fabrication such lattices to plate-like structures that, under compression, will experience out of plane elastic instabilities; such structures could be artificially restrained to remain planar, in which case all the results of the present work will hold, or under tension, without restraint, the lattice is expected to follow the results obtained in section 2.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this work to a wide variety of technological application is enhanced by the recent fabrication of mechanical meta-materials on micro/nano scale through use of nanomembrane technologies 9 and digital printing techniques 55 57 . The use of nanomembrane technologies restricts the fabrication such lattices to plate-like structures that, under compression, will experience out of plane elastic instabilities; such structures could be artificially restrained to remain planar, in which case all the results of the present work will hold, or under tension, without restraint, the lattice is expected to follow the results obtained in section 2.1.…”
Section: Discussionmentioning
confidence: 99%
“…When a material deviates from this behavour (that is to say, it has a negative Poisson’s ratio) it is termed auxetic 1 . Auxetic materials are of broad interest across the sciences 2 – 6 due to their wide range of potential applications including novel fasteners 7 , biomedical use 8 , particle filters 9 , scaffolds for reconfigurable metasurfaces 10 , and energy damping/transmitting devices 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrate that the ratio of maximum stresses in the intermediate material to those in the lamellae can be manipulated over orders of magnitude through alterations in the geometry of the structure. These findings are of particular relevance given the recent growth of digital manufacturing techniques that allow the fabrication of two-dimensional structures with features on the nano or micro length scale [51]. In many areas of application, the materials to be joined may be specified by the functionality of the desired structure, and thus η is set by the application.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified that nanomembranes are the ideal platform for such nano-optomechanical reconfigurable metamaterials [65]. Metamaterials on structured membranes can be reconfigured thermoelastically [66], mechanically [67], electrically [68] and magnetically [69]. They can also be reconfigured by the light-induced forces that occur between elements of illuminated metamolecules.…”
Section: Developing Metamaterials Technology: Switching and Tunabilitymentioning
confidence: 99%